Measuring salivary cortisol in biobehavioral research: A systematic review and methodological considerations - Fanghong Dong; Justine S. Sefcik; Elizabeth Euiler; Nancy A. Hodgson (Brain, Behavior, & Immunity - Health)
The assessment of salivary cortisol in community settings has gained popularity in biobehavioral research due to its noninvasive sampling, ease of handling and storage, and suitability for repeated sampling in short intervals. Ensuring consistent methodological practices for salivary cortisol is essential. This systematic review critically examines salivary cortisol collection procedures, data cleaning, and analysis to better understand its role in biobehavioral research within community populations. Fifty-eight articles met the inclusion criteria. Results indicated significant variability in study designs and cortisol measurement procedures, particularly regarding the biobehavioral role of cortisol, sampling periods, covariate considerations, cortisol analysis parameters, and data analysis plans. The review highlights commonly used and promising study designs while identifying methodological issues in cortisol measurement and analysis that should be addressed to improve comparability in future research.